ANALISA WAKTU DAN BIAYA DENGAN METODE EARNED VALUE ANALYSIS PADA PEKERJAAN PROYEK PEMBANGUNAN JEMBATAN - Revisdah, Revisdah; Arfan, Muhammad; Jonizar, Jonizar; Arravi, Rajulian Nurkholis (Universitas Muhammadiyah Palembang, 2023)
Due to the intricacy of the challenges that arise during the execution of work, a significant amount of thework that is done does not conform to the one that was intended. Neither on time, quality, nor the price,which is something that sometimes happens overbugdet. To be successful in overcoming this obstacle, youwill need to have excellent cost, quality, and time management.Using the Value of Results Method is oneof the many ways that construction work may be handled in an efficient and straightforward manner. Thisstudy's objective is to arrive at an estimate of the time and money required to complete the project interms of how much it will effect the cost if it happens. Using the Earned Value Analysis approach is theresearch method that will be used to determine how to assess the value of the outcomes on projectperformance in terms of time and cost as well as the expected amount of time needed to finish the project.Based on the application of the results value that was studied during a period of 54 weeks, it wasdiscovered that the completion of the project would experience an acceleration of work, specifically for74.4 weeks, when the anticipated duration was 76 weeks. This was discovered after the results value wasexamined within a period of 54 weeks. In the meanwhile, when it came to the expenses of the job, it didnot come out as expected, which was Rp. 71.424.373.019. The ultimate sum of all costs associated withthe project was Rp 66.081.465.169. The fact that there is a gap of -Rp.5.342.907.850 between the overallcost of the work and the cost of the plan indicates that the project will be profitable.